Knowledge, attitudes and practices of clinician management of adults presenting with acetylcholinesterase inhibitor poisoning - Redant, Dean Patrick (University of the Witwatersrand, Johannesburg, 2024)
Background: Acetylcholinesterase inhibitor (AChE-I) poisoning is a common cause of deliberate self-harm in South Africa (SA). Whilst there is existing literature on the epidemiology and management of AChE-I poisoning, there is a lack of research on the South African clinician’s knowledge, attitudes and clinical practice when managing these patients. Objectives: To describe the knowledge, attitudes and practices (KAP) of clinicians when managing adult patients with AChE-I poisoning in academic emergency departments (ED) in Southern Johannesburg, Gauteng. To describe the correlation between the clinician’s demographics and experience to their knowledge, attitudes and practices in this setting. Methods: One hundred and forty-five clinicians completed a structured questionnaire used to gather data on clinicians’ knowledge, attitudes and practices (KAP) with regards to their management of patients with AChE-I poisoning. Descriptive and inferential statistics were used to analyse the data and to infer correlation between clinician’s KAP vs clinician’s demographics and experience. Results: One hundred and forty-five questionnaires from 5 EDs were completed and analysed. Of which 86 (59%) of participants were female and 59 (41%) were male. The majority of participants were under the age of 40 (84%) and employed as Grade 1 Medical Officers (39%). Years of experience were divided into <2 years, 2 – 5 years and ≥5 years with each group representing a third of the sampled population. Clinician average knowledge scores on AChE-I poisoning were good (77.9% n= 12.46/16) with scores improving predictably with years of experience (72.5% in <2 years to 83% in ≥5 years). Attitudes towards managing patients with AChE-I poisoning were overall neutral. Clinician practices varied greatly, particularly with adjustment of atropine infusions and adjunctive treatments used. Conclusion: Clinicians had an overall good knowledge of AChE-I poisoning which improved predictably with greater experience managing these patients. Practices were highly varied across all demographic groups despite access to protocols in most departments studied. Attitudes were generally neutral with no clear impacting factors. Clinicians agreed unequivocally that the public health system did not provide sufficient primary preventative care in order to address the underlying factors driving patients to self-harm. This research revealed that the medical and psychosocial management of adult patients with AChE-I poisoning can be improved upon through specific clinician training.
A Research Report submitted in partial fulfillment of the requirements for the degree of Masters of Medicine in Emergency Medicine to the Faculty of Health Sciences , School of Clinical Medicine, University of the Witwatersrand, Johannesburg 2024
Keywords: Acetylcholinesterase inhibitors; Poisoning; Organophosphate; Emergency Department; Self-harm; Self-poisoning; Knowledge; Attitudes; Practices; UCTD; SDG-3: Good health and well-being